Epidemiological and clinical characteristics of children with pertussis: a 6-year retrospective cohort study in Chengdu, China - Yang, Qing; Wang, Dong-Mei; An, Qi; Huang, Liang (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to analyze the epidemiological characteristics and clinical features of hospitalized children with pertussis who were admitted to the Chengdu Public Health Clinical Center (CPHCC), China from 2018 to 2023.MethodsWe conducted a retrospective, anonymized study in children who were diagnosed with pertussis from January 2018 to December 2023 at the CPHCC. Univariate and multivariate Cox regression and the autoregressive integrated moving average model were used for identifying risk factors, and epidemiological trend analysis was performed.ResultsWe analyzed the data of 643 children with pertussis, 351 (54.59%) were younger than 6 months and 344 (53.50%) had a positive contact history. The mean (standard deviation) length of hospital stay was 8.6 (2.8) days. The median (interquartile range) number of days of coughing to the hospitalization time was 15 (12–20). In these patients, the most common clinical manifestations included a cough in 643 (100%), pneumonia in 364 (56.61%), paroxysmal spasmodic cough in 193 (30.02%), pulmonary rales in 175 (27.22%), and hoarseness of voice in 145 (22.55%). The most common complications were cardiomyopathy in 295 (45.88%) patients, liver damage in 255 (39.66%), and bronchopneumonia in 178 (27.68%). Univariate analysis and multivariate Cox proportional hazard model analysis suggested that an older age was beneficial for discharge from hospital (P < 0.05). However, patients who were treated with methylprednisolone and sulfamethoxazole had a longer length of hospital stay (both P < 0.05). An older age of onset, heavier weight, and therapeutic use of azithromycin contributed to a shorter length of hospital stay (all P < 0.05). A time series analysis showed a stable and predictable increase in pertussis cases.ConclusionsHeightened clinical and public health focus is needed for children with pertussis, particularly infants younger than 6 months. Public health investments should be increased, and specific measures should be developed to monitor and standardize the management of pertussis through multiple channels to interrupt the large-scale spread of this disease. Clinically, methylprednisolone is not recommended for treating pertussis.